2014
DOI: 10.1111/deve.12034
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Labor Market Effects of Remittances in Latin American and Caribbean Countries: Do Thresholds Exist?

Abstract: The labor market effects of remittances have long been examined in the empirical literature. To date, the results have been mixed: some authors observe a negative association between remittances and unemployment while others report that remittances increase unemployment. This study empirically examines the impact of remittances on unemployment using macroeconomic data for a sample of 18 Latin American and Caribbean countries. Specifically, the study tests whether there is a nonlinear relationship between the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A substantial body of scholarship has focused on the effects of international migration on labor force participation outside subsistence agriculture of nonmigrating family members. While the connection between migration and labor supply in sending areas is complex and context-specific (Chami et al 2011;Jackman 2014;Lo ´pez-Feldman and Escalona 2017), most studies conclude that migration discourages nonmigrating household members from engaging in paid employment, largely because remittances sent by migrants meet household financial needs. For example, Rodriguez and Tiongson (2001) found that in the Philippines international labor migration is associated with lower levels of labor force participation among nonmigrating relatives.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of scholarship has focused on the effects of international migration on labor force participation outside subsistence agriculture of nonmigrating family members. While the connection between migration and labor supply in sending areas is complex and context-specific (Chami et al 2011;Jackman 2014;Lo ´pez-Feldman and Escalona 2017), most studies conclude that migration discourages nonmigrating household members from engaging in paid employment, largely because remittances sent by migrants meet household financial needs. For example, Rodriguez and Tiongson (2001) found that in the Philippines international labor migration is associated with lower levels of labor force participation among nonmigrating relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Drinkwater et al (2009) find an insignificant relationship between unemployment and remittances for a panel of 20 countries (where remittances are equivalent to at least 1 per cent of GDP). Jackman (2014) obtain an inverted V-shaped relationship between remittances and unemployment in Latin American and Caribbean countries: remittances and unemployment are correlated positively (negatively) if the remittances-to-GDP ratio is lower (higher) than 3.25 per cent. Posso (2012) finds that remittances have a positive effect on the labour force participation rate in a panel of 66 developing countries.…”
Section: Remittances Unemployment and Informal Work: Insights From The Literature Theoretical Channels And Hypotheses To Be Testedmentioning
confidence: 88%
“…Drinkwater et al (2009) find an insignificant relationship between unemployment and remittances for a panel of 20 countries (where remittances are equivalent to at least 1% of GDP). Jackman (2014) obtain an inverted V-shaped relationship between remittances and unemployment in Latin American and Caribbean countries: remittances and unemployment are correlated positively (negatively) if the remittances-to-GDP ratio is lower (higher) than 3.25%. Posso (2012) finds that remittances have a positive effect on the labour force participation rate in a panel of sixty-six developing countries.…”
Section: Remittances Unemployment and Informal Work: Insights From The Literature Theoretical Channels And Hypotheses To Be Testedmentioning
confidence: 88%